PENYULUHAN DAN PELATIHAN DAUR ULANG SAMPAH PLASTIK SEBAGAI UPAYA PENINGKATAN NILAI EKONOMI DI KEL.BULUSAN KEC.TEMBALANG, SEMARANG - Nurhidayati Nurhidayati; Susanto Susanto (Publisher UPT P2M Politeknik Negeri Malang, 2020)
Plastic waste is one of the waste that takes a long time to decompose. The use of plastic bags is still widely encountered, especially when shopping at traditional markets or stalls. The use of plastic bags creates a lot of waste. For this reason, the community is directed to process plastic waste by providing counseling and training on using plastic bag waste to become useful and valuable items for sale. Plastic bag waste can be recycled to make useful items. Recycling is the process of turning used materials into new materials with the aim of preventing waste that can actually be useful, reducing the use of new raw materials, reducing energy use, reducing pollution, and land damage. The training is carried out by making leaf flowers and variations that can be done in other forms. Products produced from recycling plastic waste can be sold and can increase people's income.